Exploring variables influencing the prevalence of self-employed nurses in the post-pandemic context: A descriptive ecological study - Scerbo, Francesco; Verduci, Bartolomeo; Cangelosi, Giovanni; Notarnicola, Ippolito; Maurici, Massimo; Stievano, Alessandro; Rocco, Gennaro; Alvaro, Rosaria; Caggianelli, Gabriele; Mazzotta, Rocco (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background. The COVID-19 pandemic profoundly reshaped healthcare systems, accelerating ongoing structural transformations and intensifying pre-existing regional disparities in workforce distribution. Understanding the socioeconomic determinants that shape the diffusion of self-employment in nursing is essential, particularly in the post-pandemic phase, to support equitable workforce planning and the reorganization of territorial care envisioned by current national reforms. This study investigates the socio-economic factors influencing self-employed nursing practice and examines its implications for the future of Italy’s healthcare system. Methods: A descriptive ecological observational study was conducted across all 20 Italian regions. Regional-level data were collected from official administrative sources, including ENPAPI, FNOPI, ISTAT, the Ministry of Health, and C.R.E.A. Sanità. The dependent variable was the number of self-employed nurses per 10,000 inhabitants. Independent variables included average per capita income, out-of-pocket health expenditure, hospital beds per 1,000 inhabitants, and the number of National Health Service (NHS) nurses per 1,000 inhabitants. Multiple linear regression was performed, and the study followed the RECORD reporting guidelines. Results: The density of self-employed nurses varied considerably across regions, with higher values in Lombardy, Piedmont, and Aosta Valley. Among the predictors, average per capita income was positively and significantly associated with the number of self-employed nurses (β = 0.739, p = 0.001). Conversely, the number of NHS-employed nurses per 1,000 inhabitants was negatively and significantly associated with the number of self-employed nurse (β = –1.384, p = 0.001). Compared with pre-pandemic evidence, post-COVID trends indicate continuity in socioeconomic gradients but also the emergence of a substitution effect: public recruitment campaigns increased NHS staffing over 7% at the national level, with regional estimates for Lazio approaching 10%, coinciding with a proportional decline in self-employed nurses. Conclusion: Self-employment in nursing appears to operate as a flexible response to workforce shortages rather than a purely autonomous professional choice. Regional socioeconomic disparities continue to shape its distribution, with wealthier areas supporting dual public-private care markets.